Malignancy rate of atypia of undetermined significance/follicular lesion of undetermined significance in thyroid nodules undergoing FNA in a suburban endocrinology practice: A retrospective cohort analysis. Issue 10 (18th October 2018) - Seagrove‐Guffey, Maighan A.; Hatic, Haris; Peng, Haoran; Bates, Kimberly C.; Odugbesan, A. Ola
Abstract: Background: The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) was created to establish a standard terminology regarding thyroid nodules that can be shared between endocrinologists, pathologists, radiologists, and surgeons. Since its inception and use in 2009, multiple large hospitals and academic institutions have performed retrospective studies to compare their classification rates, specifically those of atypia of undetermined significance (AUS) and follicular lesion of undetermined significance (FLUS), with the recommended rates created by the National Cancer Institute. The current study compared AUS/FLUS rates at a private suburban endocrine practice with those of previous publications from large institutions and the rates established by the National Cancer Institute. Methods: Charts from 893 patients with fine‐needle aspiration (FNA) performed in 2015 were reviewed. Data specific to thyroid aspirates classified as AUS/FLUS were organized into whether patients underwent surgery, underwent subsequent repeat FNA, or required continued observation. These results then were calculated to reveal the rate of malignancy in the AUS/FLUS category with surgical pathology in the study institution. Results: A total of 893 patients underwent FNA, with 43 patients (4.82%) shown to have AUS/FLUS. A total of 21 patients proceeded to undergo thyroidectomy or lobectomy, with 7 patients (33.3%) found to have papillary or follicular thyroid carcinoma. Conclusions: The rate of use of the AUS/FLUS category for thyroid nodules examined at the study institution was found to be within the recommended range set forth by TBSRTC. However, the malignancy rates on histopathology in the study institution were found to be higher than the new proposed malignancy rates from TBSRTC published in 2017. This finding is comparable to those of multiple other community and academic institutions performed prior to and after institution of the new guidelines. Abstract : The Bethesda System for Reporting Thyroid Cytopathology has assisted in providing uniform results regarding thyroid pathology. However, atypia of undetermined significance (AUS)/follicular lesion of undetermined significance (FLUS ) remains a challenging category to manage definitively. The current study endorses treatment decisions based on current guidelines and individual patient characteristics.